DARI HUKUM KE CINTA: REORIENTASI ETIKA DALAM FIKIH PERKAWINAN ISLAM - Muhammad Ahmad Fulka Sa'dibih (Tamaddun, 2024)
This article seeks to reinterpret Islamic marital jurisprudence (fiqh al-nikāḥ) from the perspective of ethics and spirituality. For centuries, discussions on Islamic marriage law have often centered on legal-formal aspects—such as contracts, rights and obligations, and divorce rulings. Yet, beneath this juridical construction lies a deeper ethical vision: the formation of a family grounded in love (mahabbah), compassion (rahmah), and moral responsibility (amānah). Through a hermeneutical reading of classical texts such as Iḥyā’ ‘Ulūm al-Dīn by al-Ghazālī and Zād al-Ma‘ād by Ibn Qayyim al-Jawziyyah, as well as ethical insights from contemporary thinkers like Fazlur Rahman and Muhammad Abid al-Jabiri, this article argues that Islamic law should serve as a path toward love rather than a barrier to human expression. Thus, the reorientation of ethics in Islamic marital jurisprudence represents an effort to revive the spirit of ihsān amid the formalism of legal discourse. Keywords: Reorientation; Ethics; Islamic Marital Jurisprudence; Islam.